Snow Australia cross country athlete pathway (Snow Australia, 2021)
Snowsports is a sport for all, whether it`s participating recreationally with family and friends, or competitively in snowsports event. With approximately 1.2 million Australians participating in various forms of skiing and snowboarding, it is one of Australia`s largest and most popular participation sports. Whatever the motivation for participating in Snowsports, Snow Australia is committed to providing a clear "Pathways to High Performance" strategy, to educate and inform the Snowsports Community as to the stages of athletic development To assist with this important initiative, Snow Australia has developed discipline specific Snow Australia Pathway `blueprints`, informed by the Australian Institute of Sport`s (AIS) FTEM (Foundation, Talent, Elite and Mastery) Athlete framework. The blueprint provides an evidence-based and practicable approach for supporting the `whole of sport` pathway continuum and the three key outcomes of sport being: